Path Dependency and Path Plasticity: the Co-evolution of Institutions and Innovation - the German Customized Business Software Industry - Simone Strambach (Philipps-University Marburg, Department of Geography, 2008)
Path dependence and the co-evolution of technology and institutions is a key concept to understand the dynamics of structural change at the level of firms, sectors and multi-level spatial scales. The concept of path dependency is often used in economic geography to explain the economic specialisation and long-standing success as well as crises and economically unfavourable development of regions. The understanding of the institutional dynamics within a well-established technological and institutional development path of territorial settings is a central but to a large extent also an open issue. The paper focuses on the role of institutions and modes of institutional change in path dependent processes of innovation, knowledge accumulation and competence building in innovation systems. Processes of institutional change are mainly seen either as incremental, leading to continuity of the present technological path or as abrupt and disruptive, leading to the breakdown and replacement of institutional settings. By using the notion of 'path plasticity' the paper argues that paths are not coherent in themselves. There is 'path plasticity', which describes a broad range of possibilities for the creation of innovation within a dominant path of innovation systems. Plasticity results among others from the elastic stretch of institutions and institutional arrangements and their interpretative flexibility through actors. Associated with this approach, the paper takes a closer look at path plasticity, its relation to institutional change and the role of geography. Empirical evidence is provided by exploring the evolution of the German software industry. Although comparative disadvantages are caused by the established institutional setting of the national innovation system, a sub sector of this industry - customized business software - was able to become internationally competitive. The customized business software industry can be seen as an example of innovation and successful change in what is described as non- favourable institutional settings.
Keywords: 330